Magnetosheath Filamentary Structures Driven by Foreshock Energetic Ions. Issue 9 (30th August 2022) - Wei, Xinhua; Cai, Chunlin; Yang, Junying; Ma, Yuduan
Abstract: Previous simulation studies have revealed the formation of magnetosheath filamentary structures by foreshock energetic ions. We report Cluster and Double Star observations of three such events triggered by a foreshock bubble, a hot flow anomaly and a traveling foreshock, respectively. In each case, in association with the onset of foreshock energetic ions, the magnetosheath energetic ion fluxes have quasi‐periodic modifications. Their azimuthal and pitch angular distributions indicate that these populations flow into the magnetosheath along the magnetic field lines. As a result, filamentary plasma structures form and display as a series of ion density and pressure oscillations anticorrelated to temperature oscillations. Moreover, our statistical analyses of their properties show that filamentary structures primarily form in the magnetosheath with the magnetic field lines connecting to the quasi‐parallel bow shock and under favorable formation conditions similar to those of foreshock transients. The distributions of the angles between the filamentary structure normals and the local magnetic field directions peak at 80°–90°. The transverse sizes of those filaments are in the range of 0.2–1.6 R E . Magnetosheath filamentary structures are often associated with large‐amplitude ion density and temperature perturbations comparable to the unperturbed background levels. Key Points: The formation of magnetosheath filamentary structures can link to various foreshock phenomena Filamentary structures form under favorable solar wind conditions similar to those of foreshock transients Filamentary structures are often associated with large‐amplitude ion density and temperature perturbations